Wheat grain protein accumulation and polymerization mechanisms driven by nitrogen fertilization - Yu, Z.; Islam, S.; She, M.; Diepeveen, Dean; Zhang, Y.; Tang, G.; Zhang, J.; Juhasz, A.; Yang, R.; Ma, W. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 The Authors The Plant Journal © 2018 John Wiley & Sons Ltd In wheat (Triticum aestivum) grain yield and grain protein content are negatively correlated, making the simultaneous increase of the two traits challenging. Apart from genetic approaches, modification of nitrogen fertilization offers a feasible option to achieve this aim. In this study, a range of traits related to nitrogen-use efficiency in six Australian bread wheat varieties were investigated under different nitrogen treatments using 3-year multisite field trials. Changes in the individual storage protein composition were detected by high-performance liquid chromatography. Our results indicated that wheat grain yield and grain protein content reacted similarly to nitrogen availability, with grain yield being slightly more sensitive than grain protein content, and that genotype is a vital determinant of grain protein yield. Measurement of the glutamine synthetase activity of flag leaves and developing grains revealed that high nitrogen availability prompted the participation of glutamine in biological processes. In addition, a more significant accumulation of gluten macropolymer was observed under the high-nitrogen treatment from 21 days post-anthesis, and the underlying mechanism was elucidated by a comparative proteomics study. A yeast two-hybrid experiment confirmed this mechanism. The results of this study revealed that peptidyl-prolyl cis–trans isomerase (PPIase) was SUMOylated with the assistance of small ubiquitin-related modifier 1 and that high nitrogen availability facilitated this connection for the subsequent protein polymerization. Additionally, luminal-binding protein 2 in the endoplasmic reticulum played a similar role to PPIase in the aggregation of protein under high-nitrogen conditions.